Fiber-Wireless Convergence in Next-Generation Communication Networks Systems, Architectures, and Management - Tornatore, Massimo; Chang, Gee-Kung.; Ellinas, Georgios; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book investigates new enabling technologies for Fi-Wi convergence. The editors discuss Fi-Wi technologies at the three major network levels involved in the path towards convergence: system level, network architecture level, and network management level. The main topics will be: a. At system level: Radio over Fiber (digitalized vs. analogic, standardization, E-band and beyond) and 5G wireless technologies; b. Network architecture level: NGPON, WDM-PON, BBU Hotelling, Cloud Radio Access Networks (C-RANs), HetNets. c. Network management level: SDN for convergence, Next-generation Point-of-Presence, Wi-Fi LTE Handover, Cooperative MultiPoint. • Addresses the Fi-Wi convergence issues at three different levels, namely at the system level, network architecture level, and network management level • Provides approaches in communication systems, network architecture, and management that are expected to steer the evolution towards fiber-wireless convergence • Contributions from leading experts in the field of Fiber-Wireless Convergence.
Introduction -- Future Radio Access, WiFi-LTE, LTE advanced -- Evolution and Trends of Broadband Access Technologies and Fiber-Wireless Systems -- The Benefits of Convergence through Fiber Wireless Integration and Networking -- Analog and Digitized Radio-over-Fiber -- Overview of standardization for D-RoF -- Wireless delivery of over 100Gb/s mm-wave signal in the W-band -- Systems Challenges for SDN in Fiber Wireless Networks -- Architectural Evolution and Novel Design of Fiber-Wireless Access Networks -- Advanced architectures for PON supporting Fi-Wi convergence -- BBU Hotelling in Centralized Radio Access Networks -- Rethink Ring and Young -- Next Generation PoP with functional convergence re-distributions -- Coordinated Multi-Point (CoMP) Systems -- Converged Wireless Access/Optical Metro Networks in Support of Cloud and Mobile Cloud Services deploying SDN Principles -- Conclusion and Future Topics.
Keywords: Telecommunication; Computer networks .; Microwaves, RF Engineering and Optical Communications; Communications Engineering, Networks; Computer Communication Networks